Affirmation of Islamic artists on the example of Shirin Neshat and Mona Hatoum - Tomić Tatjana (Akademija umetnosti Univerziteta u Novom Sadu, 2021)
The role of women in Islamic countries is very different from the notion of women in Europe, because the religious worldview has been dominant for centuries so much that it has subdued all other spheres of society. The struggle for equality, which has been going on for decades in the so-called Western world, in Islamic countries is just getting started. Consequently, it is not surprising that the portrayal of women and everything related to them in the art and literature of Islamic countries is limited in relation to the West. Islam is a very strict religion and forbids the display of objects that lead to fetishism, such as human figures and cult images, because it represents a threat to the creative power of Allah. In the past, Islamic women did not have the opportunity to affirm themselves in the arts, because despite the fact that Islam does not support "discrimination" between men and women, at the same time it does not defend the idea of "equality". However, the postmodern era brings a revival, and today they are finally enjoying their rights and are greatly represented on the world art scene. By presenting historical themes, the artists in a special way convey emotional messages about the suffering of individual members of the Islamic faith, and in addition define and reexamine patriarchy, feminism and fundamentalism through their works. The themes of suffering are best depicted in the work of two Islamic women, Shirin Neshat and Mona Hatoum, so this paper will talk about their opus and the way in which Muslim women are affirmed in the modern age through historical-artistic and sociological approach.